Balancing Self-Incrimination and Public Safety: A Comparative Analysis of Compelled Smartphone Unlocking in Brazilian and U.S. Legal Systems - Rafael Francisco França (Revista Brasileira de Direito Processual Penal)
This study compares how the laws in the United States and Brazil handle the use of digital evidence from smartphones in initial criminal investigations. The main goal is to understand the challenges when trying to protect the right to avoid self-incrimination while also ensuring public safety. By looking at court decisions from 2014 to 2023, the study explores how the legal systems in both countries deal with arguments for and against law enforcement being able to unlock smartphones against the will of the owner. The main issue being examined is the balance between respecting citizens' privacy rights and making sure defendants get fair treatment in the legal process. The research question driving this study is: How do Brazil and the U.S. manage the situation where law enforcement needs to unlock smartphones, while also respecting constitutional rights and public safety? To answer this question, the study looks at recent court cases from both countries and identifies important arguments about forced smartphone unlocking. The findings show problems in these legal proceedings, particularly when it comes to protecting the privacy of smartphone users and defendants' rights. A key point that comes out is that when law enforcement examines suspects' phones, it can jeopardize the proper handling of evidence and the right against self-incrimination that's protected by the Constitution. The study highlights shortcomings in the responses of the Supreme Courts of Brazil and the United States. This suggests a need for a more detailed framework that can address these challenges better and solve disagreements in lower courts. In essence, this article discusses the conflict between privacy rights and self-incrimination on one hand, and the government's duty to maintain public safety and prevent illegal evidence on the other. In conclusion, this article explores the legal issues around forced smartphone unlocking in Brazil and the United States. It not only emphasizes the importance of balancing individual rights with public safety but also calls for a more comprehensive legal approach to deal with these challenges effectively.